2011
DOI: 10.1088/0957-4484/23/3/035101
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and cytotoxicity of carbon nanotube–chitosan–phycocyanin complex

Abstract: Photodynamic therapy (PDT) or photothermal therapy (PTT) using nanomaterials has shown great prospect for cancer treatment. Phycocyanin (PC) is a photoharvesting pigment and is also an attractive candidate for PDT. The multiwalled carbon nanotube (MWNT) is a potent candidate for PTT due to its extraordinary photo-to-thermal energy conversion efficiency upon excitation with near-infrared (NIR) light. To date, although MWNT-CS complexes have been well studied, no report about the reconjugation of MWNT-CS with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…[22][23][24][25] Previous reports showed that the functionalization of CNTs with CS through surface adsorption could increase their dispersibility in the solution. [26][27] A novel immunologically modified nanotube system invented by Zhou et al 28 using glycated CS-modified single-walled CNTs resulted in highly effective tumor suppression in animal tumor models, with complete tumor regression and long-term survival in many cases.…”
Section: Dong Et Almentioning
confidence: 99%
“…[22][23][24][25] Previous reports showed that the functionalization of CNTs with CS through surface adsorption could increase their dispersibility in the solution. [26][27] A novel immunologically modified nanotube system invented by Zhou et al 28 using glycated CS-modified single-walled CNTs resulted in highly effective tumor suppression in animal tumor models, with complete tumor regression and long-term survival in many cases.…”
Section: Dong Et Almentioning
confidence: 99%
“…55 Functionalization of CNTs can be achieved by using oligonucleotides, biomolecules, surfactants, and polymers, (Figure 1) thus increasing the dispersibility of CNTs and decreasing their cytotoxicity. [56][57][58][59] In a study comparing CNTs dispersed either through functionalization or with the help of a surfactant, it was revealed that fCNTs had low cytotoxicity, whereas the surfactant-dispersed CNTs in turn showed less toxicity than pristine CNTs. 17 Reports have also shown that the highly water-soluble modified SWCNTs had low agglomeration and were taken up into the cells without distressing cell viability.…”
Section: Advantages and Applications Of Functionalized Cntsmentioning
confidence: 99%
“…Therefore, CS has been widely studied for biomedical and pharmaceutical applications such as drug delivery, cancer therapy, and biosensors. 56,119,120 CNTs modified with CS are being used for the removal of heavy metals from aqueous solution, 122 as biomaterials for tissue engineering, 123 and in delivery of molecules. 119 A novel biomaterial -MWCNT-CSphycocyanin (PC) -prepared by functionalizing MWCNTs with CS and conjugated to PC (photodynamic therapy and photothermal therapy agent) (Figure 4) for photodynamic and photothermal cancer therapy were tested on breast and liver cancer cell lines (MCF-7 and HepG2) and a normal liver cell line (L-O2).…”
Section: Functionalization Using Chitosanmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been studies showing that PTT has synergistic effect with PDT and could further enhance the outcome of PDT by increasing local permeability of the sensitizers 710,1617,19,21 . A few photosensitizer-inorganic nanoparticle complexes, such as chlorin e6 loaded graphene oxide and photosensitizers conjugated carbon nanotubes, silica-coated Pd/Ag nanoparticles and gold-based nanoparticles, have been developed for applications in PTT/PDT dual therapy 710,1617,19,2123 . However, to achieve dual PTT/PDT function, these nanoparticles were required to be activated under multiple-wavelength lasers (e.g.…”
Section: Introductionmentioning
confidence: 99%